ALPAS (ALleviating PAndemic Severity) Through Foresight: Capping the Digital Divide - Romeo B Sotto; April Z Luzon; Seth B Barandon; Jocelyn O Jintalan; Maria Joy I Idian; Estelito R Clemente; Marlon S Pontillas; Harold Jan R Terano; Juvy M Bustamante; Filmor J Murillo (Camarines Sur Polytechnic Colleges, 2023)
Everyone has lost their footing due to the pandemic. The academic community was unprepared, leaving both professors and students bewildered and without a sense of direction. The goal at the time was to overcome the calamity of educational discontinuity. Sustainable Development Goal (SDG) 4 - Education goal aims "to ensure inclusive and equitable quality education and promote lifelong learning opportunities for all" relative to this SDG and the surge of the pandemic, digital divide become prominent, altering the course of educational landscape in all levels across public and private institutions. In the Bicol region, education was delivered in many various forms and variability, predicting the future through strategic foresight could propel the region to a transformed future. This paper discusses in detail the status of education in the region and the possible scenarios using Jim Dator's Future Scenario Archetypes, Causal Layered Analysis and through Scenario Planning Plus. Four plausible scenarios have surfaced in this paper: STUG-nation of Education, Unstable and Disarray of Educational elements, Flowing-restrained Education, and ORAGON Education. It requires multiple drivers as examined through the PESTEL that includes political, economic, social, technological, environmental, legal aspects. This study proved useful in crafting and anticipating the future scenarios of Bicol Region's education. Preliminary as it may, this study highlighted important building blocks of future scenarios through foresight methods. Dator's framework was proved to be very useful in developing the four scenarios, the use of other future study tools will further amplify plausible scenarios for the education of Bicol region and beyond.